The influence of different root canal irrigants on the push-out bond strength of AH plus and Bioceramic sealers - Alaa M Naeem; Iman M Al-Zaka (College of Dentistry/ University of Baghdad, 2021)
Background: The bond strength of endodontic sealers with dentin is a very important property for maintaining the integrity and seal of the root canal filling. The aim of this study was to evaluate and compare the effect of various irrigants (QMix, 17% EDTA and 2.5% NaOCl) on the push-out bond strength of AH plus and Bioceramic sealers. Materials and methods: Forty eight freshly extracted maxillary first molars human teeth with striaght palatal root were used in the study. The collected samples were randomly divided into three groups of equal sample size (n=16), according to the final irrigation regimen as follows: Group (1): QMix 2 in 1, Group (2): 17% ethylenediaminetetraacetic acid, Group (3): 2.5% sodium hypochloride. All samples were instrumented using Edge file X7 rotary instrument reaching file size 40/.04 as the final master apical file. After that each group was randomly divided into two subgroups (n=8) according to the type of sealer used: AH Plus and Total Fill BC Sealer. Obturation was conducted using single cone technique with gutta percha (GP) to all experimental roots. Two-millimeter thick slices were obtained from the middle section of the root. Bond strength of sealers was measured via a universal testing machine by using stainless steel plunger. Then, the data were statistically evaluated using two-way analysis of variance (ANOVA) and post hoc test (Bonferroni's test). Results: The push-out bond strength was significantly increased by the "irrigant" factor (P≤0.05) and by "sealer/irrigation solution" interaction (P≤0.05). Final rinse with QMix solution with BC sealer showed the highest mean value of bond strength (5.976 MPa), with a significant difference with other groups (P≤0.05), while NaOCl with AH Plus sealer showed the lowest mean value of bond strength (3.811 MPa). Conclusion: Final irrigation of the root canals with different irrigants improved the endodontic sealer's bond strength, and QMix had a positive influence on the adhesion of BC sealer.